PERCEIVED ADVERSE HEALTH EFFECTS OF EXPOSURE TO PARTICULATE MATTER AMONG RESIDENTS OF PORT HARCOURT - Clement, Emmanuel Etim; Apugo, Uchechukwu. I; Ukiwe, Okorafor Okorafor; Okoro, Sylvia Ngozi; Kenneth-Ohaeri, Christie Ugochi; Nliam, Georgeline O; Etokwudo, Onyeka Stanley, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Background: In recent years, there has been a public outcry in Port Harcourt over the presence of black particulate matter (PM) on surfaces, and in the nostrils, prompting health concerns. The study is to assess the knowledge, attitude, and perceptions of the adverse health effects of exposure to PM among residents in Port Harcourt metropolis. Method: The study was carried out using a cross-sectional design technique, while data was collected using a structured, self-administered questionnaire, administered to respondents residing in Port Harcourt during the period of public outcry, 2016 to 2020. Results: The questionnaire was administered to 400 respondents, 260 (65.0%) of whom are females. Most (96.0%) of the respondents were below the age of 50 years, of the Christian faith (96.0%), and had a tertiary education 270(67.5%). Finding from this study showed that the majority of the respondents (54.8%) have only fair knowledge of the adverse health effects of exposure to particulate matter, while 75.5% had poor attitude towards preventing the adverse health effects of exposure to PM. Most of the respondents (92.3%) in this study have poor perception towards the adverse effect of exposure to particulate matter. Conclusion: The fair knowledge of the adverse health effects of PM among the respondent translated to poor attitude and perception towards its adverse health effects. Hence, an intense sensitization is required to boost the knowledge of the populace on the adverse health effect of exposure to soot so as to increase their attitude towards preventive measures and perception of the adverse effect of the menace.